2019
DOI: 10.1103/physrevb.99.125110
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and magnetic properties of the double perovskites La2MnRuO6 and LaAMnFeO6(A

Abstract: Magnetic refrigeration at room-temperature is a technology that could potentially be more environmentallyfriendly, efficient and affordable than traditional refrigeration. The search for suitable materials for magnetocaloric refrigeration led to the study of double-perovskites La2MnNiO6, La2MnCoO6 and La2MnFeO6. While La2MnNiO6 and La2MnCoO6 are ferromagnets with near room-temperature TC s, previous theoretical study of double-perovskite La2MnFeO6 revealed that this material is a ferrimagnet due to strong elec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…It is previously established that deviation of 3 d -O-5 d bond angles from the perfect geometry of the high cubic symmetry structure ( ) in a distorted DPOs lead to a strong AFM superexchange coupling between magnetic ions, which results in a FiM ordering 46 , 50 54 and large structural distortions enhance the FiM ordering temperature 55 57 . Therefore, we displayed the DFT relaxed three peculiar TM-O-Ir bond angles on and octahedron for undoped, Cr-doped, Mn-doped, and Fe-doped LNIO materials in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is previously established that deviation of 3 d -O-5 d bond angles from the perfect geometry of the high cubic symmetry structure ( ) in a distorted DPOs lead to a strong AFM superexchange coupling between magnetic ions, which results in a FiM ordering 46 , 50 54 and large structural distortions enhance the FiM ordering temperature 55 57 . Therefore, we displayed the DFT relaxed three peculiar TM-O-Ir bond angles on and octahedron for undoped, Cr-doped, Mn-doped, and Fe-doped LNIO materials in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although the absolute value of the exchange interactions changes due to a change of U , the main trend remains unchanged. We also compared with the literature regarding the U value of the Ru, and we found that it is commonly assumed to lie between 2 and 3.5 eV [16,17,38,[66][67][68][69][70][71][72]. The combination of DOS and calculated magnetic moment suggested that Ru in this material is in the +6 nominal valance state with 4d 2 electronic configuration, with two states filled in the majority-spin channel and all remaining states in both spin channels being empty.…”
Section: F Band Structure and Density Of Statesmentioning
confidence: 87%
“…In the present compounds, the disordered perovskite layers, with different magnetic ions in multivalent states (Fe 3+/4+ , Co 2+/3+ , and Mn 3+/4+ ), possess inhomogeneous magnetic phases due to the coexistence of AFM and FM interactions. Among the possible magnetic exchange interactions, Fe involving exchange interactions are predominantly AFM and possess magnetic ordering at higher temperatures [18,39] except for Fe 3+ -O-Co 3+ [wherein Co 3+ ions will be in the low-spin state (t 6 2g , e 0 g )] and Fe 3+ -O-Mn 4+ interactions, which are FM interactions [40,41]. Further, Co 3+ -O-Mn 4+ , Mn 4+ -O-Mn 4+ , Mn 3+ -O-Mn 3+ and Co 3+ -O-Co 3+ also contribute to AFM interaction, whereas FM coupling arises from Co 2+ -O-Mn 4+ , Co 3+ -O-Mn 3+ and Mn 3+ -O-Mn 4+ [42,43].…”
Section: Thermal Variation Of DC Magnetizationmentioning
confidence: 99%
“…However, the cluster glass transition at a comparatively higher temperature (T 1 = 43 K) in FMC2 along with its ZFC and FC bifurcation (T < T 2 ) under lower applied field points to the existence of fairly strong competing AFM-FM interactions even above T 1 in FMC2. Such a peculiar magnetic feature observed in FMC2 might be due to the existence of more Fe-rich regions with AFM (Fe 3+ -O-Fe 3+ and Fe 3+ -O-Mn 3+ ) and FM (Fe 3+ -O-Mn 4+ ) interactions, which usually exhibit magnetic ordering at higher temperatures [40,58,59]. Such strong AFM-FM competing interactions are absent above T 1 in FMC1 due to dominant Co-rich regions, where the corresponding superexchange interactions may lead to the formation of a spin glass state at low temperature [34].…”
Section: E Ac Susceptibilitymentioning
confidence: 99%